Dust particles precipitation in AC/DC electrostatic precipitator. (September 2015) - Jaworek, A; Marchewicz, A; Krupa, A; Sobczyk, A T; Czech, T; Antes, T; Śliwiński, Ł; Kurz, M; Szudyga, M; Rożnowski, W
Abstract: Submicron and nanoparticles removal from flue or exhaust gases remain still a challenge for engineers. The most effective device used for gas cleaning in power plants or industry is electrostatic precipitator, but its collection efficiency steeply decreases for particles smaller than 1 micron. In this paper, fractional collection efficiency of two-stage electrostatic precipitator comprising of alternating electric field charger and DC supplied parallel-plate collection stage has been investigated. The total number collection efficiency for PM2.5 particles was higher than 95% and mass collection efficiency >99%. Fractional collection efficiency for particles between 300 nm and 1 μm was >95%.